CONTROLLED HYPERTENSION: THE EFFICACY OF PAPAYA JUICE IN LOWERING HIGH BLOOD PRESSURE IN THE ELDERLY - Bili, Maria; Damatasia, Wira; Suroso, Heri; Sulaksono, Ari Dwi (SYNTIFIC, 2024)
Background. Reducing blood pressure in the elderly can be achieved through the utilization of alternative treatments, one of which is papaya juice. Hypertension in the elderly is highly perilous and can lead to fatal consequences. This research aimed to investigate the efficacy of papaya juice consumption in lowering blood pressure among the elderly population. Research Method. This research employed a Quasi-Experimental design with a Pretest-Posttest Control Group Design. The population studied consisted of all hypertensive patients at the Mojolangu Community Health Center. Sampling was conducted using a purposive sampling technique, with a total of 30 respondents – 15 assigned to the control group and 15 to the intervention group. Data collection utilized measurement tools including a Sphygmomanometer, stethoscope, and observation sheets. Data analysis was performed using Wilcoxon and Mann-Whitney tests. Findings.